Manajemen Ekstravasasi Kemoterapi: [Extravasasion Chemoteraphy Management] - Nur Nubli Julian Parade; Isnu Pradjoko (Faculty of Medicine Universitas Airlangga, 2019)
Extravasation is a problem for patient receiving chemotherapy. This will cause pain, ulcer, necrosis and might be a permanent disability. Extravasation is a leakage of a fluid or medicine to the surrounding subcutaneous tissue of the vein or vascular, that may cause skin or tissue necrotic. There was a wide span of incidence data of extravasation on the literature, between 0,01% and 11% reported from child to adult. Management of extravasation was based on proper maintenance of the intravenous (IV) line and application of cold or warm compresses, plus the use of antidotes when available. Antidotes for extravasation that have been shown to be useful are sodium thiosulfate for nitrogen mustard, dimethylsulfoxide for anthracyclines and mitomycin, and hyaluronidase for the vinca alkaloids. New treatments include dexrazoxane, sargramostim, and hyperbaric oxygen for doxorubicin extravasations. In order to improve patient service quality and reduce morbidity, every medical staff handle cancer patient receiving chemotherapy should have sufficient knowledge about how to manage extravasation event.